The Profile of Pharmacological Treatment in Trigeminal Neuralgia Patients in The Period of January 2018-December 2018 - Marlon Yutimma Roestam Moenaf; Maftuchah Rochmanti; Devi Ariani Sudibyo (Humanistic Network for Science and Technology (HNST), 2020)
Trigeminal neuralgia is a condition that affects the trigeminal nerve, that manifests in a series of stabbing like pain, and often described like electricity. Its treatment guideline is to prioritize pharmacotherapy until patient is well. The gold standard treatment for trigeminal neuralgia is pharmacotherapy of Carbamazepine. However, carbamazepine is proven to cause allergic reaction to some patients. This research aims to describe the pharmacotherapy that is given to patients. The regiments of pharmacotherapy in trigeminal neuralgia shows that CBZ is the main pharmacotherapy given, as it is the gold standard treatment. GBP is the is the second most pharmacotherapy given and a concoction medication of Paracetamol, Diazepam and Amitriptyline being the third most favored therapy. Neurotropic B Vitamins plays a big role, as a support in the therapy to maintain the health of the overall nervous system. The pain scale data shows that almost all patients have significant pain relieve. The therapy of trigeminal neuralgia in this study shows that CBZ is most favored as it is the gold standard, however not all AEDs are accessible. Almost all patients have significant pain relieve eventhough not using gold standard treatment. Keywords: trigeminal neuralgia; pharmacotherapy